Service Quality (SERVQUAL) Dimensions on Customer Satisfaction: Empirical Evidence from Bank Study - Sigit Sugiarto; Vivi Octaviana (Golden Ratio of Marketing and Applied Psychology of Business, 2021)
This study aims to determine how much influence service quality dimensions have on customers' satisfaction who use BRI services. The model used in this study is observation, interviews, questionnaires, and literature study using a Likert scale. The method of determining the sample used is 96 respondents. The analytical method used is the multi-linear regression method. The results of this study indicate that all variables are simultaneously serviced quality dimensions consisting of Tangible (X1), Reliability (X2), Responsiveness (X3), Assurance (X4), and Empathy (X5) together have a positive influence. Partially found services consisting of Tangible, Reliability, and Empathy have a positive and significant influence on customer satisfaction. At the same time, the quality of service which consists of Responsiveness and Assurance is not supported. Service quality is a critical aspect to satisfying the customers and retaining their loyalty, so they continue to buy from you in the future. Service quality is a comparison of customer expectation and the actual delivery of service. Service quality generally refers to a customer's comparison of service expectations related to a company's performance. A business with a high level of service quality is likely capable of meeting customer needs while also remaining economically competitive in their respective industry.